Structure of flora of plant communities with Chamaecytisus graniticus (Rehmann) Rothm. (Fabaceae Lindl.) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Taxonomical, biomorphological, ecological, coenotical and geographical structure of the flora of plant communities with paleoendemic Chamaecytisus graniticus Rothm. (Fabaceae Lindl.) are studied with its autphytosozological analysis.
Keywords: Chamaecytisus graniticus, plant communities, structural analysis, rare species.